Feasibility of Parylene C for encapsulating piezoelectric actuators in active medical implants - Kohler, Alina; Blendinger, Felix; Müller, Sonja; Mescheder, Ulrich; Bucher, Volker (Frontiers in Medical Technology, 2023)
Parylene C is well known as an encapsulation material for medical implants. Within the approach of miniaturization and automatization of a bone distractor piezoelectric actuators were encapsulated with Parylene C. The properties of the polymer were investigated on its stretchability with respect to the encapsulation functionality of piezoelectric chips. We determined a linear yield strain of 1% of approx. 12 µm thick Parylene C foil. The Parylene C encapsulation withstands the mechanical stress of a minimum of 5 • 10 5 duty cycles by continuous actuation. The experiments demonstrate that elongation of the encapsulation on piezoelectric actuators and thus the elongation of Parylene C up to 0.8 mm is feasible.